CHATGPT AND THE DECLINE OF CRITICAL THINKING AMID MISUSE OF AI SYSTEMS: A COMPREHENSIVE REVIEW (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Artificial intelligence (AI) technologies — including generative language models such as ChatGPT — are increasingly becoming an integral part of education, scientific research, and daily activities. At the same time, concerns are growing that their improper or excessive use may lead to a decline in critical thinking ability. High-quality, independent thinking is a core human competence in analyzing, evaluating, and making decisions based on theoretical and practical knowledge, serving as an essential component of educational and social efficiency. This article examines the effects of incorrect use of AI systems on critical thinking, related empirical research and statistical findings, as well as potential solutions.